A hyperspectral and multi-angular synthetic dataset for algorithm development in waters of varying trophic levels and optical complexity - J. Pitarch; V. E. Brando; V. E. Brando (Earth System Science Data)
This data paper outlines the development and the structure of a new synthetic dataset within an extended optical domain, encompassing inherent and apparent optical properties (IOPs and AOPs) alongside associated optically active constituents (OACs). Bio-optical modeling benefited from knowledge and data accumulated over the past 3 decades, enabling the imposition of rigorous quality standards and the definition of novel bio-optical relationships that are significant contributions on their own. Employing the HydroLight scalar radiative transfer equation solver, above-surface and submarine light fields between 350 and 800 nm at 1 nm steps were generated, facilitating algorithm development and assessment for present and forthcoming hyperspectral satellite missions. A smaller version of the dataset, delivered at 12 Sentinel-3 Ocean and Land Colour Instrument (OLCI) bands (400 to 753 nm), was also produced, targeting multispectral sensor algorithm research. Derived AOPs encompass an array of above- and below-surface reflectances, diffuse attenuation coefficients, average cosines, and Q factor. The dataset is distributed in 5000 files, each encapsulating a specific IOP scenario, ensuring sufficient data volume for each represented water type. AOPs are resolved across the complete range of solar and viewing zenith and azimuthal angles as per the HydroLight default quadrants, amounting to 1300 angular combinations. This comprehensive directional coverage caters to studies investigating signal directionality, which previously lacked sufficient reference data. The dataset is publicly available for anonymous retrieval via the FAIR repository Zenodo at https://doi.org/10.5281/zenodo.11637178 (Pitarch and Brando, 2024).